A qualidade de águas superficiais e subterrâneas na Bacia do Rio da Prata/São Luís Maranhão sob efeito da ação antrópica - Almeida, João Batista (2013)
The of the watershed Rio Prata, in São Luís, is an important protected area located in the vicinity of the State Park Bacanga, and contributes to the water reservoir that supplies the potato São Luís . Although with small occupation, the area already shows signs of human action, identified by the presence of landfills, deforestation and river siltation. In this study, samples were collected from 14 drilled wells, 01 dug well, 02 springs and 02 points in the lake of the river, one in the middle and one near the dam. Physicochemical and hydrochemical measurements, heavy metals, inorganic, and bacteriological analysis, totaling 26 parameters, were performed on samples collected from wells every two months and the springs and lake collected monthly; sampling was initiated at the end of the dry period dry and ended in the following one. The electrical conductivity measurements in groundwater show three distinct groups of wells: com EC < 50 S/cm, com 50 < EC < 200 e com EC > 200 S/cm, the spring waters and the lake had EC in range 40-59 S/cm. The Ca2+, Mg2+, Na+ , K + , anions Cl- , SO4 2- , HCO3 - , hardness and TDS in all samples had concentrations below the VMP, color and turbidity had values above the VMP in some samples. Metals and inorganic compounds analyzed, only iron and aluminum only in sampled wells, concentration> VMP; nitrogen of only one sample of ammonium nitrate and one had a concentrations above VMP. Coliforms and E. Coli were present in all samples from springs and the lake and import of samples from wells, in very high numbers, some high values of total coliforms were not associated with the presence of E. Coli. We observed the effect of pumping water from the lake to the Batatã dam. The results of measurements of electrical conductivity and iron concentrations show two aquifers and the presence of clayey-sandy lenses.